Protótipo de uma ponte rolante - Salvadori, Thalita Lopes (2018)
Freight transportation can be problematic when it is large and/or very heavy. An alternative to making this type of work less difficult is to use a crane, which is commonly used in industries, workshops and smaller companies. The control of the bridge can be carried out by radio frequency with the programmable logic computer (CLP) or microcontroller with serial communication. This work consists in the design of a prototype of a crane, performing the positioning of the main car at the desired coordinates. For this will be used an arduino pototyping platform with serial communication. The structure is based on wood, metal rods for main car movement and for process control, the arduíno.